Future perfect?: god, medicine and human identity - Deane-Drummond, Celia (T & T Clark International, 2006)
Introduction: Future perfect? Or, what should we hope for? Peter Manley Scott and Celia Deane-Drummond -- Perfect humans or trans-humans? Ted Peters -- Human nature and the human condition Gordon Graham -- The nature of human welfare Søren Holm -- In whose image? Representations of technology and the 'ends' of humanity Elaine Graham -- In the waters of Babylon: the moral geography of the embryo Michael S. Northcott -- Neuroscience and the modification of human beings D. Gareth Jones -- Ensoulment revised in response to genetics, neuroscience and out-of-body experiences Gordon McPhate -- Medicine, science and virture Neil Messer -- Forecasting the future: legitimizing hope and calming fears in the embryo stem-cell debate Jenny Kitzinger and Clare Williams -- Never too late to live a little longer? The quest for extended life and immortality: some ethical considerations Ulf G͏̈örman -- Genetic perfection, or fulfulment of creation in Christ? Maureen Junker-Kenny -- Future perfect? God, the transhuman future and the quest for immortality Celia Deane-Drummond -- Saving us from ourselves: christology, anthropology and the seduction of posthuman medicine Brent Waters